Herbal therapies in gastrointestinal and hepatic disorders: An evidence-based clinical review - Yao, Yongfang; Habib, Murad; Bajwa, Hajra Fazeelat; Qureshi, Anina; Fareed, Rameesha; Altaf, Reem; Ilyas, Umair; Duan, Yongtao; Abbas, Muhammad (Frontiers in Pharmacology, 2022)
The gastrointestinal tract (GIT) and the liver constitute the major organs of the human body. Indeed, the very survival of the human body depends on their proper functioning. Because the GIT is a huge and complex organ system, the maintenance of proper GIT and liver health is an arduous task. GIT disturbances such as diarrhea, stomach ache, flatulence, constipation, nausea, and vomiting are very common, and they contribute to a significant burden on the healthcare system. Pharmacies are full of over-the-counter pharmacological drugs to alleviate its common conditions. However, these drugs do not always prove to be fully effective and patients have to keep on living with these ailments without a proper and long-term solution. The aim of this review article is to present a practical reference guide to the role of herbal medicines in dealing with gastrointestinal and hepatic disorders, which is supported by systematic reviews and evidence-based trials. People have depended on herbal medications for centuries for the treatment of various ailments of the GIT, liver, and other organ system problems. Recently, this trend of incorporating herbal medication for the treatment of various diseases in both developing and developed countries have surged. Many people continue to use herbal medications, even though substantial data about their efficacy, uses, and toxicological effects do not exist. In addition, while herbal medicines have enormous benefits in both the prevention and the treatment of medical ailments, they can also have toxicological effects. It is, therefore, of the utmost importance that appropriate time, energy, and resources are spent on the development of ethnopharmacology. In addition, herbal products should be classified in a pattern similar to pharmacological medications, including their uses, side effects, mechanism of action, efficacy, and so on.